Kappa chain maturation helps drive rapid development of an infant HIV-1 broadly neutralizing antibody lineage - Cassandra A. Simonich (Nature Portfolio, 2019)
Development of broadly neutralizing antibodies (bnAb) against HIV-1 in infected adults is a multi-step process unachievable by current vaccine approaches. Here the authors reconstruct the ontogeny of an infant bnAb, which develops in fewer steps, and identify its unique features that may shorten the path to HIV vaccines.